Proceedings of the 9th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management 2017
DOI: 10.5220/0006513202750282
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Learning Recommendation System Architecture for Learning Management System

Abstract: The information on the web is ever increasing and it is becoming difficult for students to find appropriate information or relevant learning material to satisfy their needs. Technology Enhanced Learning (TEL) is an area which covers all technologies that improve students learning. Effective Personal Learning Recommendation Systems (PLRS) will not only reduce this burden of information overload by recommending the relevant learning material to the students of their interest, but also provide them with "right" i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…English learning is an individual situation that differs from student to student. Thus, Syed et al (2017) revealed that English learners were continuously building on their study online courses. The Moodle circumstance created an ideal scenario where each student's education was individualized while still collaborative since students collaborated and were supported by the English lecturers or instructor.…”
Section: Discussionmentioning
confidence: 99%
“…English learning is an individual situation that differs from student to student. Thus, Syed et al (2017) revealed that English learners were continuously building on their study online courses. The Moodle circumstance created an ideal scenario where each student's education was individualized while still collaborative since students collaborated and were supported by the English lecturers or instructor.…”
Section: Discussionmentioning
confidence: 99%
“…The main idea of SFLA-RF is to assign a weigh value to each tree in RF, and the values are searched for the optimal solution by SFLA. Its establishment steps are as follows [22]:…”
Section: Proposed Sfla With Rf Algorithmmentioning
confidence: 99%
“…Alguns trabalhos buscaram implementar abordagens com base em teorias pedagógicas aplicadas a diferentes grupos de estudantes [Dorc ¸a et al 2016, Syed et al 2017, Zia and Usman 2018. No trabalho de [Syed et al 2017] foi proposto um ambiente para recomendac ¸ão que baseia-se no comportamento de grupos de estudantes para realizac ¸ão das recomendac ¸ões.…”
Section: Sistemas Para Recomendac ¸ãO De Objetos De Aprendizagemunclassified
“…Alguns trabalhos buscaram implementar abordagens com base em teorias pedagógicas aplicadas a diferentes grupos de estudantes [Dorc ¸a et al 2016, Syed et al 2017, Zia and Usman 2018. No trabalho de [Syed et al 2017] foi proposto um ambiente para recomendac ¸ão que baseia-se no comportamento de grupos de estudantes para realizac ¸ão das recomendac ¸ões. Já no trabalho de [Zia and Usman 2018] foi proposto um ambiente para recomendac ¸ão que baseia-se na teoria dos jogos para propor uma recomendac ¸ão específica com base no comportamento do estudante.…”
Section: Sistemas Para Recomendac ¸ãO De Objetos De Aprendizagemunclassified